Determination of optimal fluoroscopic angulations for aorto-coronary ostial interventions from coronary computed tomography angiography - Hell, Michaela; Schlundt, Christian; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2020)
Background: An optimal aorto-coronary angiographic projection, characterized by an orthogonal visualization of the proximal coronary artery, is crucial for interventional success. We determined the distribution of optimal C-arm positions and assessed their feasibility by invasive coronary angiography. Methods: Orthogonal aorto-coronary ostial angulations were determined in 310 CT data sets. In 100 patients undergoing subsequent invasive angiography, we assessed if the CT-predicted angulations were achievable by the C-arm system. If the predicted projection was not achievable due to mechanical constraints of the C-arm system, the most close, achievable angulation was determined. Patient characteristics were analyzed regarding the distribution of optimal angulations and its feasibility by the C-arm system. Results: For the left ostium, CT revealed a mean angulation of LAO 23 ​± ​21°/cranial 25 ​± ​23° (90% of patients with a LAO/cranial angulation, 3% LAO/caudal, 4% RAO/cranial, 3% RAO/caudal) and were achievable by the C-arm system in 87% of patients. For the right ostium, the mean CT-predicted orthogonal angulation was LAO 36 ​± ​37°/cranial 36 ​± ​51° (84% LAO/cranial, 2% LAO/caudal, 14% RAO/caudal) and achievable by the C-arm system in 45% of patients. For the left ostium, a higher body weight was associated with a steeper LAO/cranial angulation being less feasible by the C-arm system due to mechanical constraints. Conclusions: Orthogonal aorto-left coronary angulations show a relative narrow distribution predominately in LAO/cranial position whereas a wider range of angulations was found for the right coronary ostium. The feasibility of CT-predicted angulations by the C-arm system is more restricted for the right than the left coronary ostium.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Angulation; Computed tomography angiography; Coronary intervention; Ostial lesion